Effect of various zinc oxide nanoparticles in membrane photocatalytic reactor for Congo red dye treatment - Hairom, Nur Hanis Hayati; Mohammad, Abdul Wahab; Hassan Kadhum, Abdul Amir (ScienceDirect, 2014)
The utilisation of titanium dioxide (TiO2) in a coupling system membrane photocatalytic reactor (MPR) has been widely investigated. However, there have been very few studies regarding the zinc oxide (ZnO) photocatalyst in MPR, although it has been shown to provide better efficiency than TiO2 in certain cases, mainly for dye photodegradation. In this study, the influence of ZnO nanoparticles in MPR has been investigated for Congo red (CR) dye treatment. Four types of ZnO were synthesised via the precipitation of oxalic acid and zinc acetate solutions. The X-ray diffractometry (XRD) and transmission electron microscopy (TEM) results showed that precipitation is a valuable method for producing the smallest particle size (7–30 nm) of ZnO without any agglomerations, especially under stirring conditions in the presence of PVP (ZnO-PVP-St). As expected, the ZnO-PVP-St presented the great potential in MPR in terms of the highest photodegradation efficiency and lesser membrane flux decline, which was supported by the FESEM results. From the EDX analysis, it was confirmed that the small amount of ZnO-PVP-St did not pass through the membrane pores to the final stream. It was believed that the other remaining ZnO was reused in the photocatalytic reactor, for the continuous process of MPR. Due to the effective surface area of ZnO-PVP-St and adsorption of UV light, the optimum photocatalyst loading for the system was 0.3 g L1 under 20 mg L1 dye concentration and pH 7 of the initial CR dye solution